2002
DOI: 10.1099/0022-1317-83-8-1861
|View full text |Cite
|
Sign up to set email alerts
|

Identification of radically different variants of porcine reproductive and respiratory syndrome virus in Eastern Europe: towards a common ancestor for European and American viruses

Abstract: We determined 22 partial porcine reproductive and respiratory syndrome virus (PRRSV) ORF5 sequences, representing pathogenic field strains mainly from Poland and Lithuania, and two currently available European-type live PRRSV vaccines. Also, the complete ORF7 of two Lithuanian and two Polish strains was sequenced. We found that Polish, and in particular Lithuanian, PRRSV sequences were exceptionally different from the European prototype, the Lelystad virus, and in addition showed a very high national diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
88
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(92 citation statements)
references
References 51 publications
3
88
0
1
Order By: Relevance
“…Forsberg et al (19) confirmed the scant isolate variation in these countries but found diversity to be high among type 1 PRRSV when isolates from Italy and Denmark were included in the analysis. ORF 5 phylogenetic analysis also revealed a tight clustering of isolates from The Netherlands, Great Britain, France, and Belgium around LV, but quite divergent strains were shown to be present in Eastern Europe (67). Although high genetic variability is common among North American type 2 isolates, these new U.S. type 1 isolates cluster around the LV isolate despite their wide geographic distribution, suggesting a common source of entry into the United States.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Forsberg et al (19) confirmed the scant isolate variation in these countries but found diversity to be high among type 1 PRRSV when isolates from Italy and Denmark were included in the analysis. ORF 5 phylogenetic analysis also revealed a tight clustering of isolates from The Netherlands, Great Britain, France, and Belgium around LV, but quite divergent strains were shown to be present in Eastern Europe (67). Although high genetic variability is common among North American type 2 isolates, these new U.S. type 1 isolates cluster around the LV isolate despite their wide geographic distribution, suggesting a common source of entry into the United States.…”
Section: Discussionmentioning
confidence: 98%
“…Several members of the nidovirus order have been shown to undergo high-frequency recombination (50,81,83). Because of unique recombinatorial properties (81,83), widespread persistence, intermingling of virus types, and changes in swine management, PRRSV has been a key subject of evolutionary interest (17,18,19,33,39,67,69).…”
mentioning
confidence: 99%
“…Actually, the N-glycan at position 46 is very close to Cys 50 , the residue presumed to be involved in GP 5 -M protein linkage (Verheije, 2002). In this respect it is remarkable that the sole PRRSV strains known to lack the N-glycan at position 46 instead have a nearby glycosylation site at position 37 (Mateu et al, 2003;Stadejek et al, 2002), suggesting that these glycans can adopt each other's function. As GP 5 -M disulphide-bond formation is essential for arterivirus assembly (Snijder et al, 2003;Verheije, 2002), an effect of the GP 5 -N46Q mutation on this process might explain the reduced mutant virion production levels.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the European type isolates have been considered as less variable. However, the latest studies show a significant genetic heterogeneity within the European type isolates (Indik et al, 2000;Stadejek et al, 2002). Radically different variants of PRRSV in Eastern Europe support the hypothesis that the European and American genotypes of PRRSV evolved from a common ancestor (Stadejek et al, 2002).…”
mentioning
confidence: 72%